Hidden osteophyte formation on plain X-ray is the predictive factor for development of knee osteoarthritis after 48 months – data from the Osteoarthritis Initiative. Issue 3 (March 2015) - Katsuragi, J.; Sasho, T.; Yamaguchi, S.; Sato, Y.; Watanabe, A.; Akagi, R.; Muramatsu, Y.; Mukoyama, S.; Akatsu, Y.; Fukawa, T.; Endo, J.; Hoshi, H.; et al.
Summary: Objective: To examine whether the detection of osteophytes anywhere in the knee could serve as a pre-radiographic biomarker for osteoarthritis (OA) development. Methods: Baseline magnetic resonance imaging (MRIs) of 132 participants in the Osteoarthritis Initiative (OAI) were studied. Based on radiographs, 66 knees were assessed as osteoarthritis-free (no-osteoarthritis [NOA], or Kellgren/Lawrence [K/L] severity grade 0/1 both at baseline and 48 months), and another 66 knees were assessed as having radiographic OA changes (pre-radiographic osteoarthritis [PROA], or with K/L grade 0/1 at baseline and grade ≥2 at 48 months). Using baseline MRI data, we examined eight sites of osteophyte formation: the medial and lateral femoral condyle (MFC and LFC, respectively); medial and lateral tibial plateau (MTP and LTP, respectively); medial and lateral facets of the patellofemoral joint (PM and PL, respectively); tibial spine (TS); and femoral intercondylar notch (IC). Knee joint osteophyte size was assessed via the 8-point marginal osteophytes item of the whole-organ magnetic resonance imaging score (WORMS). The frequencies and distributions of osteophytes were compared between groups. Results: Mild-size osteophytes (defined as score ≥2) were observed more frequently at the MFC ( P  = 0.00278), MTP ( P  = 0.0046), TS ( P  = 0.0146), PM ( P  < 0.0001), PL ( P  = 0.0012), and IC ( P  < 0.0001) in PROA knees than in NOA knees. Moderate-size osteophytes (defined as score ≥4) were more frequently observed in PROA knees than in NOA knees only at the IC ( P  < 0.0001). Conclusion: Knees with osteophyte formation at the IC, even those of K/L severity grade 0/1, are at risk for the development of radiographic OA by 48 months.